Effectiveness Of Blended Learning In Human Anatomy Courses - I Nyoman Gede Wardana (Publikasi Indonesia, 2021)
It is very demanding to teach anatomy in the present curriculum of medical education. The amount of time allotted to teach and learn human anatomy is diminishing. The traditional teaching method is no longer effective in being able to provide vast amounts of human anatomy learning material. Besides, this method is also passive, which is not liked by the current generation of students. Various disciplines have widely used the learning approach with the blended learning method. This study aims to compare the effectiveness of the blended learning method (BL) with the traditional teaching (TT) method on the student's final grades and the percentage of graduation rates for the gross human anatomy courses. A total of 217 final student grades from Batch 2016 (69 students), Batch 2017 (69 students), and Batch 2018 (79 students) were collected and analyzed. Students in Batch 2018 received the blended learning (BL) method while the Batch 2016 and Batch 2017 received the traditional teaching (TT) method. The mean final scores between the BL and TT methods were compared, also the percentage of graduation rates between the two methods. There was a significant mean difference in the student's final grade (P <0.001) between the BL method (66.77) versus the TT method (47.84). The percentage of students who passed with the BL method (65.82%) is higher than the TT method (10.14%). The result concluded blended learning method is more effective in increasing the final grade and percentage of graduating students than the traditional teaching method for gross human anatomy courses.